Heterogeneity of primordial germ cells - Nguyen, Daniel H. (Curr Top Dev Biol, 2019)
Primordial germ cells (PGCs) must complete a complex and dynamic developmental program during embryogenesis to establish the germline. This process is highly conserved and involves a diverse array of tasks required of PGCs, including migration, survival, sex differentiation, and extensive epigenetic reprogramming. A common theme across many organisms is that PGC success is heterogeneous: only a portion of all PGCs complete all these steps while many other PGCs are eliminated from further germline contribution. The differences that distinguish successful PGCs as a population are not well understood. Here, we examine variation that exists in PGCs as they navigate the many stages of this developmental journey. We explore potential sources of PGC heterogeneity and their potential implications in affecting germ cell behaviors. Lastly, we discuss the potential for PGC development to function as a multistage selection process that assesses heterogeneity in PGCs to refine germline quality.